Development Of Puji (Emoji Puzzle) Learning Media Assisted By Picture Cards To Improve Emotional Intelligence Of Children Aged 4–6 Years - Isti Cintami Sarikasdani; Nita Priyanti; Chandra Apriyansyah (Kirana Publisher (KNPub), 2026)
This study aims to develop an emoji puzzle assisted by picture cards to improve the emotional intelligence of children aged 4–6 years. The background of the study indicates that some children at TK Cinta Ibu experience difficulties in identifying and expressing their emotions, while others are not yet able to recognize the emotions of their peers. The limited availability of learning media specifically designed to support emotional intelligence development has become a major challenge in early childhood education institutions. This study employed a Research and Development (R&D) approach using the Four-D model (Define, Design, Develop, Disseminate). The define stage involved needs analysis through observation and interviews. The design stage produced a puzzle prototype representing eight basic emotions (happy, sad, angry, afraid, surprised, shy, proud, and disgusted) supported by contextual situation cards. The develop stage included expert validation and a limited trial using a one-group pretest–posttest design with 30 children (10 children aged 4–5 years and 20 children aged 5–6 years). Effectiveness was analyzed using the Normalized Gain (N-Gain). The results show that the emoji puzzle model is theoretically feasible, highly valid according to expert evaluation, and moderately effective in improving children’s emotional intelligence.